Kinematic characteristics of a sprinting technique and morphofunctional structures of its providing - Druz, V. A.; Iermakov, S. S.; Pugach, Ya. I.; Shesterova, L. Ye.; Zukow, W.; Cieślicka, M. (Journal of Education, Health and Sport, 2017)
Druz V. A., Iermakov S. S., Pugach Ya. I., Shesterova L. Ye., Zukow W., Cieślicka M. Kinematic characteristics of a sprinting technique and morphofunctional structures of its providing. Journal of Education, Health and Sport. 2016;6(11):271-280. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166766 http://ojs.ukw.edu.pl/index.php/johs/article/view/3998 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 15.11.2016. KINEMATIC CHARACTERISTICS OF A SPRINTING TECHNIQUE AND MORPHOFUNCTIONAL STRUCTURES OF ITS PROVIDING Druz V. A.1, Iermakov S. S.2, Pugach Ya. I.1, Shesterova L. Ye.1, Zukow W.2, Cieślicka M.2 1Kharkov State Academy of Physical Culture 2Kazimierz Wielki University in Bydgoszcz Abstract Introduction The overall performance of a coach and the efficiency of performances of sportsmen are defined completely by the depth of understanding of regularities which are the cornerstone of the mechanisms, which provide the performance of competitive exercises. The most comprehensive investigations of these questions in track and field athletics are devoted to studying of sprint that significantly promoted the improvement of the process of a coach (Yefremenko, 2013 -2015; Shesterova, Yanhao, 2014-2016). However, the uniform generalization in the received scientific results isn't reached. It considerably reduces the overall performance of a coach. The optimization of the training process and the efficiency of performance of a sportsman are defined by the depth of knowledge of the interdependent relations of kinematic and dynamic characteristics of the performed physical actions and their connections with the morphofunctional educations, which provide their implementation. At the same time the final result depends on the motive endowments of a sportsman, the level of preparedness and the current functional state. The purpose of the research. To present the uniform system of the interdependent relations of the biomechanical and physiological regularities which provide the fastest movement of the general center of body weight GCBW of a sportsman when passing by him the established distance of run and to establish the structure of creation of an optimum algorithm of the training process taking into account individual physical development of a sportsman on the basis of provisions of the theory of training. The achievement of the purpose defined the need of the solution of the following tasks: 1. To carry out the analysis of literature and to systematize scientific achievements on the considered problem. 2. To select the fundamental laws of mechanics which define kinematic and dynamic characteristics of movement of biokinematic links and center of mass (GCBW). On the basis of what to establish the coherence of movement of GCBW with a speed of movement of biokinematic links. 3. To define the communication between intensity of the performed work and the duration of its preservations depending on the level of preparedness of the the corresponding morphofunctional mechanisms which provide its performance. 4. To develop the method of creation of an optimum algorithm of ensuring physical preparedness of a sportsman taking into account his specific features of physical development and physical state. Material and methods Analytic survey of scientific data on the questions of the research of sprint and mechanics of movement of a body in supported and unsupported phases of its movement; construction of semantic sign spaces with the uniform measure entered into them that allows to compare the share importance of parameters of various dimension at their contribution to the achievement of the final result; mathematical modeling of interaction of functional systems in dynamics; methods of analogy and similarity of manifestation of the principles of the interacting systems in preservation of their equilibrium state. Results The analytical expressions which describe a trajectory of movement of GCBW of a body and CBW of two biokinematic link pendulums are established on the basis of laws of mechanics. Circles of cycloid, parabola, helicoid concern to them. It allowed, using the method of mathematical modeling, to establish the specific features of the performance of walking and run inherent in a concrete somatotype. A type of a constitution is defined at which it is possible to develop the run speed when the phase of a support can become less than phase of a flight, that provides extremely possible speed of movement of GCBW of a sportsman on the basis of the results of the researches of videograms of run of the ex-world record-holder in run on 100 m Asafa Powell, the works of Mil Koch, Kadzh Tomazin, Stephanie Letzelter, Akira Ito, Masaki Ishivaka, etc., and also the executed model constructions. Conclusion The modern requirements of the development of sport define conditions of the organization of the training process in which it is necessary to provide the systematic control and the analysis of dynamics of the passing changes in biomechanics of the mastered movements, physiological processes of the training and competitive loads providing performance, psychological preparedness of the sportsman for extreme and special conditions. The implementation of such control demands the corresponding preparation of the coach's structure and necessary technical providing. The existence of modern control methods of the dynamics of the development of exhaustion in change of movements of biokinematic links of a body allow to carry out in real time on video filming this task. However, the coach can't provide the performance of all these functions at full satisfaction of these conditions. The trained professional has to be appropriately in ensuring the training process, and the training in the contents has to consist of not only the direct physical activities, but also the subsequent analysis of the video record of the actions and computer processing of their performance. The solution of these tasks assumes opening of the new specialization in specialized educational institutions, which provides the scientific and technical maintenance of the educational-training process and competitive performances. It is natural that the solution of this task has to be carried out step by step, but now there are all bases to start the beginning of its realization. Key words: kinematic characteristic, sprinting technique, morphofunctional structures.